Genetic affinity and admixture of northern Thai people along their migration route in northern Thailand: Evidence from autosomal STR loci - Kutanan W. (2014)
The Khon Mueang (KM) are the largest group of northern Thai people. Our previous mtDNA studies have suggested an admixture process among the KM with the earlier Mon-Khmer-speaking inhabitants of this region. In this study, we evaluate genetic affinities and admixture among 10 KM populations in northern Thailand lying along the historical Yuan migration route, and 10 neighboring populations belonging to 7 additional ethnic groups: Lawa, Mon (Mon-Khmer-speaking groups), Shan, Yuan, Lue, Khuen and Yong (Tai-speaking groups) by analyzing 15 hypervariable autosomal short tandem repeat loci. The KM exhibited close relationships with neighboring populations, especially the Tai-speaking groups, reflecting an admixed origin of the KM. Admixture proportions were observed in all KM populations, which had a higher contribution from the parental Tai than the Mon-Khmer groups. Different admixture patterns of the KM along the migration route might indicate high heterogeneity among the KM. These patterns were not directly associated with geographical proximity, suggesting other factors, like variation in the timing of admixture with the existing populations may have had an important role. More genetic data from different marker systems solely transmitted through the male or female lineages are needed to complete the description of genetic admixture and population history of the KM. © 2011 The Japan Society of Human Genetics All rights reserved.